Increasing Nurses' Commitment Through Managing Role Conflict, Role Unclarity and Job Stress in the Hospital - Boby Krismanto Pello; Hasyim; Rokiah Kusumapradja (International Journal of Nursing and Health Services (IJNHS), 2025)
Background: Hospitals are organizations that provide health services. Objective: The objective of this study is to examine the impact of role conflict, role ambiguity, and work stress on the organizational commitment of nurses. Method: This study utilized a cross-sectional technique to investigate the correlation between the independent variables and the dependent variables. The population consists of all nurses employed at Eka Hospital Bekasi. The sampling technique employed was purposive random sampling, with a sample size of 88 respondents. Result. The findings indicate a favorable correlation between role conflict, role ambiguity, and work-related stress on organizational commitment at Hospital Bekasi. Recommendation: Further study needs to conduct the to conduct a cross-sectional study to assess the impact of job stress on nurses' quality of life and caring behaviors, and identify factors that contribute to excessive job stress among nurses.